2007
DOI: 10.2478/s11658-007-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen regulation and ion dependence of taurine uptake by MCF-7 human breast cancer cells

Abstract: It has been reported that estrogen receptor-positive MCF-7 cells express TauT, a Na + -dependent taurine transporter. However, there is a paucity of information relating to the characteristics of taurine transport in this human breast cancer cell line. Therefore, we have examined the characteristics and regulation of taurine uptake by MCF-7 cells. Taurine uptake by MCF-7 cells showed an absolute dependence upon extracellular Na + . Although taurine uptake was reduced in Cl -free medium a significant portion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Thus, taurine concentration seems to be related to estrogen activity in the brain. Indeed, estrogen receptors regulate taurine uptake via the Na þ -dependent taurine transporter (TauT) in MCF-7 human breast cancer cells (Han et al, 2006;Shennan and Thomson, 2007). Both estrogen receptors ERa and ERb are present in the mouse cortex, hippocampus, and striatum, although striatal levels of either messenger RNA or protein are much lower (Küppers and Beyer, 1999;Mitra et al, 2003;Shughrue and Merchenthaler, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, taurine concentration seems to be related to estrogen activity in the brain. Indeed, estrogen receptors regulate taurine uptake via the Na þ -dependent taurine transporter (TauT) in MCF-7 human breast cancer cells (Han et al, 2006;Shennan and Thomson, 2007). Both estrogen receptors ERa and ERb are present in the mouse cortex, hippocampus, and striatum, although striatal levels of either messenger RNA or protein are much lower (Küppers and Beyer, 1999;Mitra et al, 2003;Shughrue and Merchenthaler, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…An effect of Tat transgene leak also is plausible given that induction of Tat expression induces cortical edema in young Tat-tg mice [46], that Tat likely causes edema in older female Tat-tg mice [15], and that edema triggers cellular taurine loss to counter extracellular hypoosmolality [73]. Because estrogen upregulates taurine transporter activity [76] and reduces taurine efflux in an estrogen receptordependent manner consequent to glutamate excitotoxicity [77], estradiol declines in older female mice also may contribute to the especially low MPFC and striatal taurine levels we found in older female Tattg mice (Fig. 2).…”
Section: Taurinementioning
confidence: 99%
“…In that sense, taurine compromised metastasis in both breast cancer cell lines, independently of the presence of estrogen receptor. Besides, it should be noted that estrogen exerted its significant effect on taurine uptake, through increased expression of TauT transporter in MCF-7 cells (86). It has been reported that Na + -dependent uptake of taurine through TauT transporter was activated by 17β-estradiol and p53 transcription factor, as shown by experiments in MCF-7 cells (87).…”
Section: Beneficial Effect Of Taurine In Various Cancers (In Vitro Anmentioning
confidence: 89%